2021
DOI: 10.3390/land10121306
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Landscape Values and Conflicts through the Optics of Different User Groups

Abstract: The paper presents the results of the study on participative mapping of landscape values and conflicts and a subsequent interpretation of the indicated localities from respondents’ point of view. The study focused on younger groups of landscape users—lower-secondary-school students (aged 11–15) and university students (aged 20–25)—in comparison with experts’ points of view. The research presumed that the perception of landscape values and issues are determined by age, level of education and by experience in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…Yellow stickers were used to mark landscapes that they felt were most important to them before 2010, and blue stickers were used for landscapes considered most important after 2010 (Figure 3). To enhance the depth and breadth of the data, in addition to identifying and marking these locations, residents were also required to record how they perceive and interpret the landscape and its values [86]. Subsequently, a questionnaire was distributed again to the mapping participants, containing 20 items testing village development and value orientation preferences and 4 items for scoring the current village status.…”
Section: Data Collectionmentioning
confidence: 99%
“…Yellow stickers were used to mark landscapes that they felt were most important to them before 2010, and blue stickers were used for landscapes considered most important after 2010 (Figure 3). To enhance the depth and breadth of the data, in addition to identifying and marking these locations, residents were also required to record how they perceive and interpret the landscape and its values [86]. Subsequently, a questionnaire was distributed again to the mapping participants, containing 20 items testing village development and value orientation preferences and 4 items for scoring the current village status.…”
Section: Data Collectionmentioning
confidence: 99%
“…Los beneficios de usar herramientas PPGIS incluyen la comprensión de las dinámicas espaciales y temporales, beneficiarse del conocimiento del usuario, incorporar los valores de la población local, aumentar el compromiso social y superar los enfoques de arriba hacia abajo (Palacio Buendía et al, 2021;Plieninger et al, 2013;Blicharska et al, 2016). Para la presente investigación, el mapeo participativo se llevó a cabo mediante el uso de la herramienta Survey 123 ArcGIS online dentro de la plataforma ArcGIS de ESRI® (Vavrouchová et al, 2021). Estos formularios se difundieron por distintos medios de comunicación oficiales de Mendoza, 1 plataformas académicas 2 y redes sociales, estando activo durante 6 meses.…”
Section: Los Valores Intangibles Del Paisaje Del Piedemonte Y Su Cart...unclassified
“…Studies have shown that the aesthetic scales of evaluators from different cultural backgrounds do not differ statistically significantly and that experts in design and university students have better aesthetic perceptions than the general public [40,41]. In particular, college students, as an urban youth population, have a gradually increasing voice in the family, and their behaviors and preferences have an impact on family travel plans.…”
Section: Respondentsmentioning
confidence: 99%